Education Leadership in K–12 Systems from a Métis Worldview: Infusing Education Leadership with an Understanding of Wâhkôhtowin - Chaulk, Dana (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
The education system in Alberta has been struggling for years to provide quality education within increasingly complex learning environments. Gaps in student knowledge and skills, neurodivergencies, background learning experiences, language competencies, social and emotional regulation levels, differing parental expectations, and other complexities all contribute to the difficulties facing today’s educators. This article explores how Métis and First Nations ways of being, knowing, and doing may be infused within a transformative approach to education leadership, which may serve to meet the challenges of the current Alberta education system. Wâhkôhtowin is discussed as a guiding principle within an education leadership framework, along with decolonializing, social justice, and culturally responsive policies as requirements to make substantive and sustainable changes within the current Alberta education system.